Fertilizantes organominerais remineralizadores do solo e micorrização na produção de Eucalyptus grandis W. Hill ex Maiden. - Stumm, Juliano de Oliveira (2020)
Animal waste can be exploited as fertilizer for the cultivation of agricultural and forest species. Organic fertilizers can be granulated with soil remineralizers to increase their nutrients, in addition to facilitating their application to the soil and when associated with soil microorganisms they can have a positive effect on plant growth. The general objective of this work was to analyze different remineralizing organomineral fertilizers and mycorrhizal fungi species in the production of seedlings and in the growth of Eucalyptus grandis. For this, three scientific works were developed: The first work consisted in selecting mycorrhizae for the formation of E. grandis seedlings cultivated with different organomineral fertilizers remineralizing the soil, for later transplantation in the field. In the second work, the objective was to enable the use of organomineral fertilizers remineralizing the soil and ectomycorrization in the growth of E. grandis. The third work aimed to test the viability of different mycorrhizal inoculants submitted to different temperatures and storage times, in the root colonization and growth of E. grandis seedlings. Organomineral fertilizers (FOM) and remineralizing organominerals (FOMREMS) did not differ from mineral fertilizers (FM) in the growth of E. grandis seedlings, formed for later transplantation, and can be indicated as efficient substitutes for nursery fertilization. The different mycorrhizal isolates had the same effect for the seedling growth variables, however, the isolate Suillus cothurnatus (UFSC-SU118) contributed to the height of plants. Organomineral fertilizers (FOM) and organomineral soil remineralizers (FOMREMS), promote greater development of Eucalyptus grandis plants after transplantation. Mycorrhization with Pisolithus microcarpus was efficient for the accumulation of phosphorus in the roots, mainly in plants cultivated with soil remineralizing fertilizer (FM + REMS). The different materials used for the production of inoculant of the fungus Pisolithus microcarpus (UFSC-PT116), had no effect on the final colonization of the roots by ectomycorrhiza. The storage temperature of the inoculants influenced the colonization of the roots of Eucalyptus grandis, where all (4º, 15º ± 1º and 25ºC) showed a reduction at 60 days.